Renewed bleeding of a posterior inferior cerebellar artery aneurysm during vertebral angiography. Issue 660 (October 1980) - Drury, P. J.; Powell, T.
Abstract : The perangiographic rupture of a posterior inferior cerebellar artery aneurysm is described and discussed. Only 2 other cases of perangiographic rupture of posterior fossa aneurysms have been found in the literature, and there are fewer than 60 reports of ruptures of aneurysms at all intracranial sites.